A variational approach to the Brown–Ravenhall operator for the relativistic one-electron atoms. (May 2016) - Coti Zelati, Vittorio; Nolasco, Margherita
Abstract: We study the Brown–Ravenhall operator (the projection of the Dirac operator perturbed by a potential V ∈ L w 3 ) using the Foldy–Wouthuysen (unitary) transformation and its realization as an elliptic problem in the 4-dim half space R + 4 with Neumann boundary condition. Using this approach we give a characterization of its eigenvalues and eigenfunctions alternative to the classical Rayleigh quotients.